A review on the electrochemical sensors and biosensors composed of nanogaps as sensing material - Dhahi, T. H. S.; Uda, Hashim, Prof. Dr.; Ahmed, N. M.; Mat Taib, A. (National Institute of Research and Development for Optoelectronics, 2010)
Link to publisher's homepage at http://inoe.inoe.ro